The Occurrence of Acute Postoperative Confusion in Patients after Cardiac Surgery - Jürgen Osterbrink; John P. McDonough; Andre Ewers; Herbert Mayer (The Scientific World Journal)
This study quantified the occurrence of acute confusion in cardiac surgery patients at three German hospitals. A total of 867 patients, 22–91 years old, were examined each nursing shift postoperatively for 5 days for the presence of acute confusion using a modified version of the Glasgow Coma Scale and Confusion Rating Scale. The night shifts and the third postoperative day showed the most frequent periods of occurrence. Confusional state was noted in patients ranging from 10.5% for patients aged <70, to 40.7% for patients >80 years of age. Those found at increased risk were patients of increasing age and coexisting disease. Targeted nursing interventions for patients at increased risk of acute confusion may decrease this complication.